No man is an island: Social coordination and the environment - Karine Nyborg (University of Oslo, Department of Economics, 2019)
Humans are fundamentally social. Social activities require coordination, which may yield multiple equilibria in the form of stable, self-reinforcing patterns of herd behavior. Since environmental impacts can differ substantially between alternative equilibria, such self-reinforcing behaviors may, from an environmental perspective, be viewed as representing virtuous or vicious cycles. Environmental policies can help break the self-fulfilling expectations of vicious cycles, tipping the economy to more environment-friendly equilibria.
Keywords: D10; D62; D91; Q01; Q50; Q58; 330; Environmental policy; multiple equilibria; social interaction; tipping points